2017
DOI: 10.1111/azo.12231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the spatio‐temporal parameters of gaits in Dasypus novemcinctus (Xenarthra: Dasypodidae)

Abstract: Armadillos comprise a particular group of armoured animals whose functional morphology of locomotion remains unclear. For the first time, the kinematic patterns of Dasypus novemcinctus are analysed. Eight specimens of nine-banded armadillos were studied at a research institute in São Paulo State, Brazil. The individuals were induced to cross a horizontal corridor and each gait performed during the time each of them was kept inside this structure was recorded to a detailed analysis posteriorly performed in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…) but is exclusively quadrupedal during locomotion (Costa et al . ). However, some species of armadillo employ plantigrade hindlimb postures and unguligrade forelimb postures during locomotion, suggesting a greater role for the hindlimbs in weight‐bearing in at least some cingulates (Vizcaíno & Milne ).…”
Section: Discussionmentioning
confidence: 97%
“…) but is exclusively quadrupedal during locomotion (Costa et al . ). However, some species of armadillo employ plantigrade hindlimb postures and unguligrade forelimb postures during locomotion, suggesting a greater role for the hindlimbs in weight‐bearing in at least some cingulates (Vizcaíno & Milne ).…”
Section: Discussionmentioning
confidence: 97%
“…matacus (M. T. Butcher unpublished data), which is less modified for scratch‐digging and classified as generalized digging as its level of fossorality (Attias et al, 2016), and is a member of the subfamily Tolypeutinae. This condition of lacking an extra shoulder stabilizer could possibly be derived for greater RoM of the forelimb, but for locomotor behavior associated with ‘cursorial’ habits of these species (Costa et al, 2019; Vizcaíno & Milne, 2002). Indeed, the latter two armadillos depend less on scratch‐digging for foraging and predator evasion, and overall less frequent burrow construction (Nowak, 2018; Smith, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The smallest armadillo species do not exceed 0.115 kg while some glyptodonts weighed more than 2,000 kg (Superina & Abba, 2018;Vizcaíno et al, 2012). Size was generally treated separately from other biological traits in taxonomic or evolutionary contributions on this group (e.g., Wetzel & Mondolfi, 1979), while other studies addressed allometry in the postcranial skeleton of armadillos from the functional, metabolic or physiological viewpoints (e.g., Frappell et al, 1998;Vizcaíno & Milne, 2002;Costa et al, 2019). However, Cardini (2019) demonstrated that extant armadillos exhibit a craniofacial evolutionary allometry similar to that of other placental mammals, a trend also detected in a comparative investigation of allometric variations between several armadillo genera (Moeller, 1968) and in two more detailed studies on euphractines (Abba et al, 2015) and dasypodines (Hautier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%